The level of awareness of community towards the implementation of vision school / Roslina Muhamad and Norazrina Mohamad Arsad - Muhamad, Roslina; Mohamad Arsad, Norazrina (Faculty of Business and Management, 2001)
What is Vision School? Regarding to statement of Deputy Minister of Education. Dato' Hon Choon Kim, Vision School is a program to bring a unity and a better relationship between student from different race in a school including from different stream. This program is still under implementation. There are two Vision Schools to be built in Subang Jaya and Johore Bahru. In this program, there are consist of three school buildings that combine Sekolah Rendah Kebangsaan, Sekolah Rendah Jenis Kebangsaan Cina (SRJKC) and Sekolah Rendah Jenis Kebangsaan Tamil (SRJKT) in one area. They share same facilities like canteen, hall, field and others. Suggestion to generate Visison Schools had been agreed by MCA and MIC. However five schools of Sekolah Rendah Jenis Kebangsaan Cina (SRJKC) that had been offered to carry out Vision Schools but they refused the offer, one in Johore, Negeri Sembilan, Kedah and two in Perak.